INCREASING INVESTMENT INTEREST BY STRENGTHENING SHARIA COMPLIANCE ON THE INDONESIAN STOCK EXCHANGE - Rahmawati, Enjellina; Nasrulloh, Nasrulloh (LPPM STIE Muhammadiah Bandung, 2023)
The purpose of this study is to explore how strengthening sharia compliance on the Indonesia Stock Exchange can increase investor interest in investing in the Islamic capital market. This study uses a qualitative method. The results show that strong shariah compliance can increase investor confidence in the shariah capital market and help attract potential investors who may not be interested in conventional investments. In addition, sharia compliance can also help minimize investment risk and increase long-term investment value.